Focal Task-Specific Lower Limb Dystonia Only When Walking Stairs: Is It a New Disease Entity? - Baik, Jong Sam; Ma, Hyeo-Il; Lee, Phil Hyu; Taira, Takaomi (Frontiers in Neurology, 2019)
Introduction: Focal task-specific dystonia in the lower limb or foot are occurred only during walking, running, hiking or cycling. Several medications and botulinum toxin injection are effective in these patients. The objective of this study was to understand of the spectrum of focal task-specific dystonia in the lower limb only when walking stairs and to compare with other types of task-specific dystonia. Methods: Using PubMed, all original articles and case reports were collected and reviewed. In addition, all video clips of published cases were evaluated, and patients’ clinical findings analyzed. The present study included 12 patients described in previous studies and five new Asian patients found in the medical records. Results: Most of them were women, and the onset age was 42 years. Ten patients were classified as the Kicking type, including three patients with the rKicking type, and six patients were considered the Lifting type; however, only one patient was not included in any of the types. Symptoms in most of all patients did not improve with any medication or botulinum toxin injection. The symptom of the most patients was not changed over a long time. Conclusion: Most patients showed the dystonic symptom when walking downstairs rather than upstairs. Psychogenic dystonia is a disease differentially diagnosed with this dystonia. Unlike other types of focal task-specific dystonia, the response to treatment was disappointing because most of the medications and botulinum toxin injection were not effective. The prognosis is completely different from other types of focal task-specific dystonia.